Comparative analysis of Colombian regulations for timber construction, compared to 6 international codes. - Guzman Zabala, Juan Francisco
For the construction of structures with timber, there are regulations that guarantee that all constructions comply with a minimum level of safety. These must be designed to protect public health, regulate structural safety, comfort and well-being of users. This article aims to identify the strengths and weaknesses of international regulations compared to the Colombian one. A comparative analysis of 7 timber building codes implemented by 13 countries was carried out, evaluating 6 variables through a Likert scale from 1 to 5. Reliability was found by applying the Cronbach's alpha coefficient (α). As a result, the countries with the highest density of construction in height with timber in the world and their 23 most representative buildings were identified, a radial graph was elaborated that allowed to identify the strengths and weaknesses for each of the evaluated standards, with a high reliability of the 0.94.